Dual PHY Layer for Non-Orthogonal Multiple Access Transceiver in 5G Networks - Sobia Baig; Muneeb Ahmad; Hafiz Muhammad Asif; Muhammad Naeem Shehzad; Mujtaba Hussain Jaffery (IEEE Access)
Non-orthogonal multiple access (NOMA) is a promising multiple access technique, proposed in literature for the fifth generation (5G) mobile networks. The NOMA system model consists of the conventional orthogonal frequency division multiplexing (OFDM), as a pulse shaping technique in conjunction with a variable power domain for various users, allocated in proportion to each user’s channel gain. OFDM technique based on wavelet filter banks, namely wavelet OFDM (WOFDM) has been utilized in digital communication to improve the system robustness to noise and adjacent channel interference, and is therefore anticipated to be adopted for the NOMA technique. WOFDM in NOMA (WNOMA) outperforms OFDM-based conventional NOMA (CNOMA) with reference to interference mitigation, bandwidth efficiency, spectral confinement, and multi-user capacity. Most of the fourth generation (4G) networks are based on OFDM and its variants. Therefore, in this paper, keeping in view the interoperability with the 4G networks and the latency requirements in 5G, a dual physical layer based on conventional OFDM and WOFDM as pulse shaping methods, is proposed for the NOMA transceiver. Performance of WNOMA and CNOMA is analyzed for bit error rate in the presence of channel impairments including additive noise and IQ imbalance and multiuser capacity is also computed. Comparison of various parameters indicates the advantage of adopting WNOMA over its conventional counterpart for relatively poor channel conditions.